Biomechanics of elite handcyclists are highly individual - a case series on kinetics, kinematics, and muscular activity - Quittmann, O. J.; Birk, C.; Göll, F.; Nolte, S.; Abel, T. (Frontiers in Sports and Active Living, 2025)
Aim: This study aimed to assess the biomechanics of handcycling propulsion under various exercise modalities in elite handcyclists with special emphasis on the work distribution between the push and pull phases.